Chemical constituents and evidence-based pharmacological properties of Physalis peruviana L.: An overview - Félicien Mushagalusa Kasali; Naasson Tuyiringire; Emanuel L Peter; Lucrèce Y . Ahovegbe; Muhammad Shaiq Ali; Jonans Tusiimire; Patrick Engeu Ogwang; Justin Ntokamunda Kadima; Amon Ganafa Agaba (Journal of HerbMed Pharmacology, 2022)
Physalis peruviana L. is among plant species possessing evident nutritional, nutraceutical, and commercial interests. This review highlights the complexity of the chemical composition supporting the multiple pharmacotherapeutic indications and dietary values of this plant through evidence-based studies from Google Scholar, PubMed/Medline, SciFinder, Science Direct, Scopus, the Wiley online library, and Web of Science. The literature mentions at least 40 compounds isolated from different parts; others are still under investigation. High yields in carotenoids, amino acids, minerals, vitamin C, vitamin E, and essential fatty acids have healthy nutritional benefits. Various phytoconstituents, particularly withanolides, exhibit anti-carcinogenic, anti-inflammatory, and antidiabetic potentials, as well as cardiovascular and liver protective effects. Prospective studies reveal that the leaves would also provide various beneficial bioactive chemicals worth being isolated. However, clinical evidence-based studies are seldom. Therefore, adequate pharmaceutical formulations and more in-depth controlled clinical trials are needed to fill the gap.